2005
DOI: 10.1124/mol.105.012435
|View full text |Cite
|
Sign up to set email alerts
|

The Amino Acid Asn136 in HIV-1 Reverse Transcriptase (RT) Maintains Efficient Association of Both RT Subunits and Enables the Rational Design of Novel RT Inhibitors

Abstract: The highly conserved Asn136 is in close proximity to the nonnucleoside reverse transcriptase (RT) inhibitor (NNRTI)-specific lipophilic pocket of human immunodeficiency virus type 1 (HIV-1) RT. Site-directed mutagenesis has revealed that the catalytic activity of HIV-1 RT mutated at position Asn136 is heavily compromised. Only 0.07 to 2.1% of wild-type activity is retained, depending on the nature of the amino acid change at position 136. The detrimental effect of the mutations at position 136 occurred when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…In agreement with the experimental data, molecular modeling of TSAO-m 3 T binding to this loop in wild-type RT suggests that the observed destabilization of the heterodimeric RT may result from structural and conformational perturbations at the RT subunit interface (Sluis- Cremer et al, 2000;Rodríguez-Barrios et al, 2001). Likewise, mutations at the 139 position of the HIV-1 RT may destabilize the p66/p51 heterodimer in a similar way, thus diminishing the catalytic activity of the enzyme as described previously for some amino acid mutations at position 138 and recently also at positions 136 (Balzarini et al, 2005) and 137 of HIV-1 RT. Indeed, a seriously compromised RT activity was observed for several amino acid mutations at position 139, especially for the lysine and aspartic acid residues, which also resulted in a higher susceptibility of the mutated RT to the inactivating (denaturation) action of urea (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the experimental data, molecular modeling of TSAO-m 3 T binding to this loop in wild-type RT suggests that the observed destabilization of the heterodimeric RT may result from structural and conformational perturbations at the RT subunit interface (Sluis- Cremer et al, 2000;Rodríguez-Barrios et al, 2001). Likewise, mutations at the 139 position of the HIV-1 RT may destabilize the p66/p51 heterodimer in a similar way, thus diminishing the catalytic activity of the enzyme as described previously for some amino acid mutations at position 138 and recently also at positions 136 (Balzarini et al, 2005) and 137 of HIV-1 RT. Indeed, a seriously compromised RT activity was observed for several amino acid mutations at position 139, especially for the lysine and aspartic acid residues, which also resulted in a higher susceptibility of the mutated RT to the inactivating (denaturation) action of urea (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…22 Several amino acid substitutions within the β7-β8 loop of p51 are known to impair heterodimer formation, while decreasing the DNA polymerase activity of the viral RT in enzymatic assays. [16][17][18] Molecular mechanisms leading to fitness recovery play an important role in antiretroviral therapy. Evolution of drug resistance is characterized by severe fitness losses, which can be partially overcome by compensatory mutations or other adaptive changes that restore viral replication capacity.…”
Section: Discussionmentioning
confidence: 99%
“…In p51, residues 52-55 and 135-140 in the fingers subdomain, 255-265 and 286-290 in the thumb subdomain, and 393-402 and 420-423 in the connection subdomain generate the largely hydrophobic surface that interacts with p66. 15 Several non-conservative mutations in p51 that affect residues of the β7-β8 loop (positions 134-139) [16][17][18][19] or the so-called "Trp motif" (residues 398, 401, 402, 406, 410 and 414) 20,21 are known to impair RT dimerization, while producing a loss of viral infectivity.…”
Section: Introductionmentioning
confidence: 99%
“…The ␤7-␤8 loop (residues 132 to 140) of the p51 but not the p66 subunit is located at the RT heterodimer interface and contributes to the formation and stability of the NNRTI binding pocket (NNRTI) (18). For instance, residues I132, I135, N136, E138, and T139 in the p51 subunit contributed specifically to NNRTI resistance (2,5,39). Moreover, previous data generated with the recombinant subunit-specific RT systems suggested that residue 139 in the p66 subunit is not involved in resistance to the F18 analogue (ϩ)-calanolide A (2, 6, 9).…”
Section: Discussionmentioning
confidence: 99%